Energy efficient electromagnetic actuated CVT system - Rahman, Mohammed Ataur; Sharif, Sazzad; Mohiuddin, A. K. M.; Rashid, Muhammad Mahbubur; Hossain, Altab (Springer, 2014)
A continuously variable transmission (CVT) system transmits the engine/battery power to the car driving wheel smoothly and efficiently.Several types of CVT already been developed to improve the transmission losses while maintaining acceleration time. However,most of the CVT has some constraints in the actuation mechanism which led us to develop an innovative electromagnetic actuator for CVT. Simplified mathematical equations have been developed for the kinematics analysis of clamping forces of the CVT and electromagnetic forces of EMA. The EMA has been developed for  scale car with two sets of solenoid. Each of the two sets has been equipped with primary and secondary pulleys for pushing and pulling the movable sheave. The solenoid is operated by controlling the supply current with a fuzzy logic controller. A simulation based fuzzy logic controller has been introduced here for identifying the desired current of the EMA actuation. The experimental results show that the EMA develops electromagnetic forces 301 N for the supply current of 3.37 amp, which makes the acceleration time of the car in the range of 2.5~3.5 sec and electromagnetic actuated CVT system highly energy efficient.